การพัฒนาทักษะการเขียนจดหมายอิเล็กทรอนิกส์ภาษาอังกฤษของนักเรียน มัธยมศึกษาตอนต้นโดยการสอนการประยุกต์ใช้ Google Translate และเครื่องมือออนไลน์ประเภทต่าง ๆ: The Development of the English Email Writing Skills of Lower Secondary School Students through the Instruction of the Integration of Google Translate and Other Online Tools - Atipat Boonmoh อธิปัตย์ บุญเหมาะ; Natkristha Kophimai ณัฐกริษฐา โกพิมาย (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The objective of this study were; 1) to compare the English writing skills of lower secondary school students in Bangkok Metropolitan between before and after learning to integrate the Google Translate application and other online tools, 2) to investigate the satisfaction of lower secondary school students in Bangkok Metropolitan who are continuing their education by incorporating Google Translate and other online tools. The participants were 35 students from Mattayomsuksa two students, Wat Sakae Ngam School, Bangkok, and Academic year 2023, selected by using cluster random sampling. The instruments used in the study were lesson plans, E-mail writing tests (Pretest/Posttest), and a satisfaction questionnaire to determine the level of student satisfaction with the learning provision based on the integration of Google Translate and other online tools. Quantitative methods were used to analyze the data. This study yielded the following results: 1. The English Writing of students was enhanced by integrating Google Translate. 2. The testing score after learning with the approach was statistically higher than before learning with the approach at the .05 level. 3. The overall result of the students’ satisfaction toward learning provision by integrating of Google Translate and other online tools was at high level.